2023
DOI: 10.3390/ijerph20021108
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Yoga Exercise on Blood Pressure and Hand Grip Strength in Chronic Stroke Patients: A Pilot Controlled Study

Abstract: Background: We investigated the beneficial effect of add-on yoga with rehabilitation on blood pressure (BP) and hand grip strength in patients with chronic stroke (more than 90 days). Methods: The study included patients 30–80 years of age who could stand independently for 1 min. Patients with psychiatric diseases or undergoing other therapies (like acupuncture) were excluded. The yoga group received training (1 h session twice weekly) with standard rehabilitation for 8 weeks. The control group received standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…The decreases observed in SBP after the yoga therapy intervention align with prior research emphasizing the potential blood pressure-lowering effects of yoga [ 14 , 15 ]. Studies have demonstrated that yoga practices, including pranayama (breathing exercises) and meditation, can trigger relaxation responses, decrease activity in the sympathetic nervous system, and enhance endothelial function.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The decreases observed in SBP after the yoga therapy intervention align with prior research emphasizing the potential blood pressure-lowering effects of yoga [ 14 , 15 ]. Studies have demonstrated that yoga practices, including pranayama (breathing exercises) and meditation, can trigger relaxation responses, decrease activity in the sympathetic nervous system, and enhance endothelial function.…”
Section: Discussionsupporting
confidence: 80%
“…Studies have demonstrated that yoga practices, including pranayama (breathing exercises) and meditation, can trigger relaxation responses, decrease activity in the sympathetic nervous system, and enhance endothelial function. These factors collectively contribute to the reduction of blood pressure levels [ 8 , 14 ]. Given the strong association between insomnia and hypertension in older adults [ 4 ], the simultaneous improvement in both measures points to yoga therapy's beneficial effects on older women's sleep and cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study shows that yoga increases the oxygen content in the blood and may increase brain activity and improve cognitive abilities, so it can be said that early yoga intervention in stroke sufferers will improve cognitive abilities. Lai et al (2023), combining yoga with rehabilitation in chronic stroke patients, has the potential to increase hand grip strength and lower blood pressure. Gender and age can also affect the outcome of rehabilitation.…”
Section: Resultsmentioning
confidence: 99%